Body Height, Estimated Cerebrospinal Fluid Pressure and Open-Angle Glaucoma. The Beijing Eye Study 2011 - Jonas, Jost B.; Wang, Ningli; Wang, Ya Xing; You, Qi Sheng; Xie, Xiaobin; Yang, Diya; Xu, Liang (PloS one, 2014)
To examine potential associations between body height, cerebrospinal fluid pressure (CSFP), trans-lamina cribrosa pressure difference (TLCPD) and prevalence of open-angle glaucoma (OAG) in a population-based setting. The population-based Beijing Eye Study 2011 included 3468 individuals with a mean age of 64.6 ± 9.8 years (range:50-93 years). A detailed ophthalmic examination was performed. Based on a previous study with lumbar cerebrospinal fluid pressure (CSFP) measurements, CSFP was calculated as CSFP[mmHg] = 0.44 × Body Mass Index[kg/m(2)] + 0.16 × Diastolic Blood Pressure[mmHg]-0.18 × Age[Years]-1.91. Data of IOP and CSFP were available for 3353 (96.7%) subjects. Taller body height was associated with higher CSFP (P<0.001; standardized correlation coefficient beta:0.13; regression coefficient B:0.29; 95% confidence interval (CI):0.25,0.33) after adjusting for male gender, urban region of habitation, higher educational level, and pulse rate. If TLCPD instead of CSFP was added, taller body height was associated with lower TLCPD (P<0.001;beta:-0.10;B:-0.20;95%CI:-0.25,-0.15). Correspondingly, higher CSFP was associated with taller body height (P = 0.003;beta:0.02;B:0.01;95%CI:0.00,0.02), after adjusting for age, gender, body mass index, pulse, systolic blood pressure, and blood concentration of cholesterol. If IOP was added to the model, higher CSFP was associated with higher IOP (P<0.001;beta:0.02;B:0.02;95%CI:0.01,0.03). TLCPD was associated with lower body height (P = 0.003;beta:-0.04;B -0.02,95%CI:-0.04,-0.01) after adjusting for age, body mass index, systolic blood pressure, pulse, blood concentrations of triglycerides, axial length, central corneal thickness, corneal curvature radius, and anterior chamber depth. Adding the prevalence of OAG to the multivariate analysis revealed, that taller body height was associated with a lower OAG prevalence (P = 0.03;beta:-0.03;B:-1.20;95%CI:-2.28,-0.12) after adjusting for educational level and gender. Taller body height was associated with higher CSFP and lower TLCPD (and vice versa), after adjusting for systemic and ocular parameters. Parallel to the associations between a higher prevalence of glaucoma with a lower CSFP or higher TLCPD, taller body height was associated with a lower prevalence of OAG.